Archaeological collections as a prime research asset: objects and Great Zimbabwe's past - Chiripanhura, Pauline (Department of Archaeology, 2018)
This thesis sought to explore the lifeways of second-millennium AD inhabitants of Great Zimbabwe through the analyses of material objects housed in museums. Great Zimbabwe comprises walled stone enclosures and non-walled settlements covering approximately 720ha. A number of data acquisition techniques, such as desktop survey, analyses of museum collections, supplementary field survey and excavations, were employed to collect relevant datasets to address the research questions. The sampling strategy adapted for this research enabled the study of material objects from different components making up Great Zimbabwe. The main conclusions drawn from this study are as follows: (i) Within varying temporal scales, the nature and distribution of local and imported objects are largely similar across the site; (ii) chronologically and typologically speaking, there is evidence that different parts of the site were occupied and abandoned at different times; and (iii) based on the similarities in material objects and associated production debris and infrastructure, it is likely that different components were self-sufficient units. This study has underscored the significance of existing collections in developing new interpretations of Great Zimbabwe's past lifeways, thereby motivating for the need for similar work to understand the hundreds of similar settlements scattered across southern Africa.